Responsibility in strategic communication : truth or trap? - Hejlová, Denisa; Koudelková, Petra; Moravcová, Hana; Romenti, Stefania; Valentini, Chiara (Advances in public relations and communication management, 2025)
Corporate social responsibility, diversity, equity, inclusion, sustainability, ESG, and environmental concerns have become paramount in the realm of strategic communication and public relations. Communicating these concepts effectively is vital to a myriad of stakeholders, encompassing both internal and external communications. How are these elements managed, articulated, and represented in modern communication practices? In today's era, marked by the burgeoning significance of digital communication, an increasing number of organizational leaders recognize the imperative of entrusting decision-making authority to communication experts. Responsibility in Strategic Communication offers a profound exploration into responsible strategic communication, differentiating genuine commitment from mere promises of responsibility. Advances in Public Relations and Communication Management(APCRM) is a publication of the European Public Relations Education and Research Association (EUPRERA). Each volume includes contributions from EUPRERA's annual congress and follow the theme of each event.